2005
DOI: 10.1002/rcm.1911
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent shift from labile to recalcitrant carbon sources of arctic heterotrophs

Abstract: Soils of high latitudes store approximately one-third of the global soil carbon pool. Decomposition of soil organic matter (SOM) is expected to increase in response to global warming, which is most pronounced in northern latitudes. It is, however, unclear if microorganisms are able to utilize more stable, recalcitrant C pools, when labile soil carbon pools will be depleted due to increasing temperatures. Here we report on an incubation experiment with intact soil cores of a frost-boil tundra ecosystem at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 50 publications
10
110
4
1
Order By: Relevance
“…The temperature sensitivity of peat mineralization, as expressed by its Q 10 value, is a useful parameter for characterizing the intrinsic decomposability of SOM (Hogg et al, 1992;Biasi et al, 2005;Davidson and Janssens, 2006;Conant et al, 2008;Boddy et al, 2008;Karhu et al, 2010;Hilasvuori et al, 2013). In line with the biochemical and elemental evidence reviewed above, it was reported to increase with increasing resistance of peat soils against OM decomposition (Scanlon and Moore, 2000), soil depth and peat age (Hardie et al, 2011;Hilasvuori et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The temperature sensitivity of peat mineralization, as expressed by its Q 10 value, is a useful parameter for characterizing the intrinsic decomposability of SOM (Hogg et al, 1992;Biasi et al, 2005;Davidson and Janssens, 2006;Conant et al, 2008;Boddy et al, 2008;Karhu et al, 2010;Hilasvuori et al, 2013). In line with the biochemical and elemental evidence reviewed above, it was reported to increase with increasing resistance of peat soils against OM decomposition (Scanlon and Moore, 2000), soil depth and peat age (Hardie et al, 2011;Hilasvuori et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast to other studies on unmanaged organic soils reporting no trend or increasing Q 10 values with depth (Scanlon and Moore, 2000; Wang et al, 2010;Hardie et al, 2011;Hilasvuori et al, 2013), the cropland and grassland profiles in our study had a lower Q 10 below the 60 cm depth. Various studies on SOM decomposition used Q 10 values as an indicator of SOM recalcitrance (Hogg et al, 1992;Biasi et al, 2005;Davidson and Janssens, 2006;Conant et al, 2008Conant et al, , 2011Hartley and Ineson, 2008;Hilasvuori et al, 2013). Considering that the presence of labile crop residues would decrease Q 10 in the topsoil rather than in the subsoil, the higher topsoil Q 10 may be explained by an extended accumulation of recalcitrant moieties.…”
Section: Co 2 Emissions and Temperature Sensitivity Of Decompositionmentioning
confidence: 99%
“…The effect of temperature on Rs has been illustrated in a wide range of studies (Eliasson et al, 2005;Fierer et al, 2005;Lloyd and Taylor, 1994;Tucker et al, 2013). Biasi et al (2005) reported that temperature could influence the utilization of carbon source by microbes or microbial metabolism leading to Rs rate changes. Treat et al (2014) found that warmer and drier climate could result in substantial increase in carbon loss (Biasi et al, 2005;Dutta et al, 2006;Treat et al, 2014).…”
Section: Effects Of Temperature and Oxygenmentioning
confidence: 99%
“…Biasi et al (2005) reported that temperature could influence the utilization of carbon source by microbes or microbial metabolism leading to Rs rate changes. Treat et al (2014) found that warmer and drier climate could result in substantial increase in carbon loss (Biasi et al, 2005;Dutta et al, 2006;Treat et al, 2014). DOC also was driven by temperature rising (Freeman et al, 2001b).…”
Section: Effects Of Temperature and Oxygenmentioning
confidence: 99%
See 1 more Smart Citation